The ambient air pollution in the Govan Mbeki Local Municipality - a time series analysis - Fokazi, Asiphe (Cape Peninsula University of Technology, 2023)
Background: Human health effects from ambient air pollution in sub-Saharan Africa has necessitated the need for an urgent need for more epidemiological studies in the global south countries due to a lack of data in these countries. Exposure information on air pollution is critical for recognizing and addressing its public health impact. In many African countries including South Africa, even though air pollution is regarded as a global risk, the spatial distribution of air pollutants has not been thoroughly quantified. This study aim therefore to quantify and compare the seasonal spatial variation of particulate matter (PM10) in the Govan Mbeki Local Municipality of Mpumalanga Province of South Africa using a time series analysis. Methods: Qualitative and quantitative research approaches were both employed. Secondary data on air quality was elicited from Secunda company, South African Coal (SASOL), and the South African Air Quality Information System (SAAQIS) website. Govan Mbeki Local Municipality was selected as an area of concern because of the industrial activities within the district. Results: The 24-hours average concentration of PM10 recorded at Embalenhle were high, far exceeded the more stringent US NAAQS and the World Health Organization guidelines. Up to 250ug/m3 24-hours concentration recorded in Embalenhle during winter of 2018. the daily concentration of PM10 at Lebohang demonstrated the lowest concentration most of the time, only showed an increase above the standard in winter of 2018 and 2020 (150 μg/m3 and 270 μg/m3 respectively). The annual average of PM10 was exceeded in Embalenhle during 2016, 2017, 2018 and 2019 (mean concentration of 51,2, 54,1,47.3 and 42,3 respectively) whereas the annual concentration of PM10 recorded at Bosjespruit exceeded the annual standard during 2019 and 2020 (mean concentration of 42,3 and 61,2 respectively) Thus, making the exposure to the pollutant dangerous to human’s health. The lowest annual average concentrations were recorded in Club-NIQI (lowest mean of 1.2) whereas the was no data recorded for the annual average concentration of Lebohang. The findings of the study also revealed that the annual and 24-hours average concentration of PM10 was within the acceptable concentration on air quality standards of South Africa during summer and autumn for all regions. During 2019, the annual concentration exceeded the annual standard by 2% in Bosjespruit (mean concentration of 42.3) and by 5% in Embalenhle (mean concentration of 45.1). During 2020, Bosjesspruit demonstrated a very high annual mean concentration compared to other regions (mean concentration of 61.9). The daily average concentration observed during lockdown was below the standard of 75μg/m3 thus making the lockdown a contributor in the reduction of the pollutant of concern. It has also been revealed that the annual mean concentration recorded from 2021-2022 was below the annual specified standard (mean concentration ranged from 24-30) for all the regions. The correlating of PM10 with meteorological factors such as temperature, and wind speed was found inversely proportional. However, the correlation of PM10 with wind direction was comparative. Therefore, when the wind direction increases, the average PM10 concentration increased most of the time too. It has also been revealed that these meteorological factors, become higher in summer while the PM10 concentration reduces and, they are lower in winter while PM10 increases in winter. Conclusions: The study concludes that the winter average concentrations were generally higher than the levels recorded in summer for the pollutant (PM10). It was also revealed that Embalenhle and Bosjespruit had the highest seasonal variation of PM10 which were observed during the winter and spring season. Lebohang had days where the 24-hours concentration exceeded the standards in winter months of 2018. Nonetheless, the concentration was below the proposed standards. The findings of the study also revealed that the lockdown contributed to the low level of 24 hours average PM10 emission because the daily concentration observed on the 27 March 2020 until 30 March 2020 was below the stipulated standard. Whilst there are no legislative guidelines to compare the current study monthly averages, the overall concentrations for PM10 were lower than the South African Ambient Air Quality Standards (SAAAQS) for criteria pollutant PM10 (1 year = 40μg/m3) in Club-NIQI. Therefore, the PM10 concentrations were still observable at a low concentration. Meaning, based on the primarily of the National Ambient Air Quality Standards (NAAQS) set thresholds for health-harmful pollution levels, the PM10 concentration was still under the acceptable amount although in Embalenhle the annual standard was exceeded during 2016-2019 which is believed to cause considerable harm to the exposed population. However, the was an improvement observed in the state of air quality from the results of the study from 2021- 2022 that shows the stipulated air quality standards are being followed in South Africa. Analysing the results obtained in Govan Mbeki Local Municipality and previous studies, a conclusion can be made, the assessment of the correlating PM10 concentration with meteorological factors, temperature, and wind speed have indicated that the correlations are all inversely associated. Therefore, when the temperature, wind speed increases, the average PM10 concentration decreases and vice versa. However, the assessment of the correlation between PM10 concentration with wind direction have indicated directly associated.
Thesis (Master of Environmental Sciences)--Cape Peninsula University of Technology, 2023
Keywords: Air quality management; Air -- Quality; Air -- Pollution; Air -- Pollution -- Health aspects; Air -- Pollution -- Computer simulation; Environmental health